IMPLIKASI KEBIJAKAN “PENDAERAHAN” PENGELOLAAN PBB SETELAH BERLAKUNYA UU NO. 28 TAHUN 2009 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH - Pamuji, Kadar (Jurnal Dinamika Hukum, 2011)
Local tax policies according to local tax laws and new levies which gives breadth to the local taxation authority is done by expanding the tax base. Giving to the local taxation authority have been duly carried out to confirm the alignments to the process of democratization. The problem is "how is the legal implications of the Land and Building Tax management of rural and urban sector after the enactment of Law no. 28 of 2009 on regional taxes and Retribution" To know the legal implications, the study begins first by performing comparative Land and Building Tax  arrangement according to the Law. 12 of 1985 by Act no. 28 of 2009 on regional taxes and Retribution. The results of the study concluded that the policy of the Land and Building Tax management of rural and urban sectors is authorized for the district/city, which has implications on the necessity for coordination, transfer of assets, preparation of executive human resources, technology, device setup, institutional arrangements, legal instruments (regulations and declaring) as well as other supporting facilities and infrastructure. Key words: Legal Implication, Policy, Land and Building Tax Management